Working but Poor: A Reassessment - Bernard Delhausse (Luxembourg Income Study (LIS), 1995)
It is widely held that people who work have no difficulty in avoiding poverty and guaranteeing their family a decent standard of living. This idea has proved false, as many authors have shown that the ranks of the poor are filled with active people, sometimes even working full time. But, previous studies have failed to consider the extent of poverty among the active and inactive poor people. Estimating Gini indices and poverty gaps for those groups gives a different idea of the working poor. To some extent it also modifies the conclusions drawn solely from the headcount ratios.
Keywords: 330; Lebensstandard; Haushaltseinkommen; Armut; USA; Kanada; Großbritannien; Schweden; Niederlande